Pelatihan Wirausaha Bagi Pelaku Usaha Mikro Kecil Dan Menengah (UMKM) Di Desa Durian Kecamatan Padang Cermin Kabupaten Pesawaran - Mawardi Mawardi; Ulil Albab; Azka Nuriah; Novia Reka; Nofan Refaldi (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this MSME training program is that the aim of entrepreneurial training is not to direct people or SMEs to create new businesses, but to help SMEs to see business opportunities and new markets by looking at them from a different angle. This different angle is more directed at the need for new innovations from businesses that are currently being run and ensuring business continuity. This activity can increase sales and profits, expand target markets, deepen customer loyalty, and increase competitive advantage (Perwita, 2021). The benefits obtained from this activity are for participants to gain knowledge and product promotion. Increased product orders from a wider target market will also be obtained. Apart from that, this activity also provides social learning for the implementing team, namely students. Students interpret the knowledge gained on campus by providing benefits to many people. Students also carry out downstream research and interpret knowledge for the progress of SMEs. Increased product orders from a wider target market will also be obtained. The method used is Participatory Action Research (PAR). From the results of the service, it can be concluded that this MSME training was carried out so that Konveksi Aura consumers would increase and expand from various regions. This MSME training uses Instagram media which will be filled with content and product videos. This video content is in the form of product manufacturing procedures, types of products produced, and profiles, pachaking designs. The content video is published on the durian village Instagram account.